Desenvolvimento e caracterização de biocompósitos de blendas TPU/PCL com hidroxiapatita para produção de scaffolds bioativos via impressão 3D - Pinto, Leonardo Alves (2022)
The increasing need for biological tissues to treat defects caused by disease or injury has demanded new solutions to provide functional substitutes that supply tissue shortages and suit the needs of each patient. In this perspective, the present dissertation sought to develop biocomposites based on polyurethane/poly(ɛ-caprolactone) (TPU/PCL) polymer blends with hydroxyapatite (HA) to produce scaffolds via 3D printing aiming tissue engineering combining biocompatibility and bioactivity with the tissue and with its ability to a relatively simple adjustment of shape and size with thermal stimulation. For this purpose, different biocomposites were produced with the matrix of TPU, PCL, and TPU/PCL blends (in proportions of 75/25, 50/50 and 75/25), with HA filler content varying up to 20% wt. These were processed in a torque rheometer. The thermal, rheological, morphological, mechanical, printability and cell line biocompatibility characteristics were investigated. The scaffolds were produced with the crushed material of the rheometer and using a 3D printer with a syringe extruder. The results of the thermal, rheological and mechanical characterizations showed that the blends and the biocomposites from them showed intermediate behavior between the TPU and PCL matrices and their respective biocomposites with HA. The addition of HA intensified degradation reactions, mainly of the TPU matrix. In test with cell line in plates from TPU, blends of 75/25 and biocomposites with up to 10% wt of HA in these matrices, the results showed that such formulations allow cell proliferation. The scaffolds produced with the blend of 75/25 and biocomposites with up to 10% wt, showed high values of fixation (≥ 71%) and shape recovery (≥ 90%) at a temperature of 55 ºC for 20 s. The mechanical properties of the printed scaffolds exhibited values close to the threshold required for human cancellous bone grafting.